Digital Marketing Capability and Firm Performance in B2B Industrial Ecosystems: The Parallel Mediation of Market Agility and Customer Relationship Quality - Nuraeni; Agustini Tanjung; Sri Wahyuningsih; Riana Oktaviani (Global Research Collaboration, 2026)
Global industrial ecosystems are undergoing digital transformation, yet business-to-business (B2B) firms often report that technological investments do not consistently improve financial or operational performance, a phenomenon termed the